Strategi Pemasaran Usaha Tanaman Hias Aglonema: (Studi Kasus Di Suluh Nursey Batanghari Lampung Timur) - Ahmad Rifai; Dewi Mareta; Lilis Renfiana (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research uses the theory put forward by Kotler and Keller regarding the marketing mix which is divided into 7Ps (product, promotion, price, place, people, process, and physical evidence) to discuss marketing strategies for aglonema ornamental plants in one of the aglonema cultivation sites in Batanghari , East Lampung. This research aims to reveal the marketing strategies used by Suluh Nursery Aglonema to increase sales of their ornamental plants. This research is qualitative descriptive research or field research. The method used to collect data is observation, interviews and documentation. Based on the research conducted, the marketing strategy at Suluh Nursery Aglonema is to increase sales by promoting Aglonema ornamental plants on various social media such as TikTok, YouTube, Facebook and WA. Apart from selling online, Suluh Nursery Aglonema also sells offline to the public.